GENESIS DAN KLASIFIKASI TANAH YANG BERKEMBANG DI ATAS BATUAN INDUK GRANIT DI TAMAN NASIONAL LORE LINDU - Rachmat Zainuddin (Universitas Tadulako, 2015)
The study on soil formation based on toposequenceof granite parent rock at LoreLinduNational Park is a pedology study to understand specific characteristics of soil developed on graniteparent rock. The study began from October to December 2015, and conducted in three phases, namely field study, laboratory analysis, and descriptive data analysis. On the same parent material, three representative profiles were investigated, and then the chemistry, physic, and mineralogy were analyzed. The representative profile determination was based on geological map, topographical map, and general vegetation condition in field. Comparison between one profile and others used similarity index calculation. The field profiling showed that the same horizon on the three representative profiles, namely Ah, Bw, BC, C, and similarity index indicated that there are more similaritiesamongprofiles G1, G2, and G3. It islikely due to the rock formation existed in one toposequence tract of land was mutually continued, so that a part of soil of rock profile existing in the upper position was transported into the lower profile. All soil profiles began to develop on early phase characterized by dominant montmorillonite clay mineral of 2:1 type. The soils of the G1, G2, and G3 profiles are classified into Humic Cambisols according to FAO/UNESCO (1997) whereas according to PPT (1983) they are classified into Cambisols Distric and according to the Soil Taxonomy System (1998) classified into Humid Dystrudept. Keywords: Classification, Genesis, Granite, Lore Lindu, Soil, Topography.